Peran Literasi Digital sebagai Variabel Mediasi dalam Hubungan Implementasi Artificial Intelligence terhadap Kinerja Karyawan pada Industri Jasa Keuangan Syariah - Djaelani Susanto; Subarjo Subarjo; Dwi Lesno Panglipursari; Busthanul Arifin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the effect of Artificial Intelligence (AI) implementation on employee performance with digital literacy as a mediating variable in the service sector. The research adopts a quantitative approach using survey data from 300 respondents and is analyzed through Structural Equation Modeling (SEM) with AMOS 24. The results show that AI implementation has a positive and significant effect on digital literacy, indicating that the adoption of AI technology encourages employees to enhance their digital skills and adaptability. However, the direct influence of AI implementation on employee performance is found to be insignificant, suggesting that technology alone cannot improve productivity without adequate human readiness and organizational support. Furthermore, digital literacy significantly affects employee performance and fully mediates the relationship between AI implementation and employee performance. This finding implies that the successful adoption of AI requires not only technological investment but also the development of employees’ digital competencies. Theoretically, the study reinforces the role of digital literacy as a strategic enabler for technology-driven performance improvement in the era of digital transformation